ENERGY ABSORPTION STUDY OF FLEXIBLE ELASTIC DOT MATRIX SUPPORT BASED ON DLP PROCESS - FANG Chuang; JI XiaoGang; DENG Lin; WANG Wei (Jixie qiangdu)
In order to meet the structural design and prototyping requirements of micro multi-functional brackets, a study on the design and preparation of flexible elastie dot matrix brackets based on digital light processing (DLP) rapid forming process was carried out. Based on the geometric topology design of the cell structure, the equivalent mechanical model of the cell structure was established by using Timoshenko beam theory to obtain a mathematical model for predicting energy absorption, and the influence of cell geometry and load direction was analyzed in focus. The novel flexible photosensitive resin was used as the forming material , and the DLP forming process was selected to realize the high-precision and high-efficiency preparation of the corresponding dot matrix structure. Combining numerical simulation and physical experiments, the effects of rod diameter, cell edge length and number of dot matrix layers on the energy absorption characteristies of the dot matrix structure were investigated. The results show that the out-of-plane compression of the dot matrix structure has significantly better energy.